THE EFFECT OF INCREASING THE MINIMUM WAGE ON POVERTY AND INEQUALITY IN BOSNIA AND HERZEGOVINA - Kurta, Amela; Oruč, Nermin (Economic Annals, 2020)
The minimum wage, as a labour market policy with distributive im-pact, is widely debated in Bosnia and Her-zegovina (BiH). This paper estimates the effect of increasing the minimum wage on poverty and income inequality in BiH, pro-viding the first empirical evidence on the minimum wage in the country. Using data from the Household Budget Survey (HBS) for 2015, the effects of four changes (two per entity) in the minimum wage were simulat-ed using the microsimulation model BiH-MOD. First, the effect of the latest changes implemented in the previous period was calculated using the previous minimum wage level as the baseline. Second, the effect of recently proposed changes was simulated using the current level as the baseline. The findings suggest that increasing the mini-mum wage in BiH has a significant positive effect on poverty reduction, but a limited effect on the level of income inequality. The estimated effects were also calculated for different types of households. The results suggest that a single policy may have unex-pected effects if other policies are not taken into account and harmonized accordingly. The findings provide empirical evidence for decision-makers and future policy debate, which is generally missing for this and simi-lar policy issues in BiH.